Maxillary Single Complete Denture with Metal Mesh Reinforcement: A Case Report - Bhandari, A; Thakur, SN; Khanal, B; Mishra, S (Journal of Nepalese Prosthodontic Society, 2022)
Single complete denture opposing natural dentition is common occurrence in daily practice. Opposing natural dentition could be completely or partially edentulous. Fabrication of single complete denture is always challenging to the dentists. It is difficult to achieve balanced occlusion in such cases because the remaining natural dentition could be extruded from socket, tilted or mispositioned. Heat cured denture base resins are most commonly used material for fabrication of denture but they tend to fracture when it is opposed by the natural dentition. The use of a metal mesh in denture base for reinforcement offers many advantages in such cases. This case report presents a case of fabrication of maxillary single complete denture with metal mesh opposing natural dentition in lower arch.